Mouse Models of Prostate Cancer. (11th January 2011) - Valkenburg, Kenneth C.; Williams, Bart O.
Abstract : The development and optimization of high-throughput screening methods has identified a multitude of genetic changes associated with human disease. The use of immunodeficient and genetically engineered mouse models that mimic the human disease has been crucial in validating the importance of these genetic pathways in prostate cancer. These models provide a platform for finding novel therapies to treat human patients afflicted with prostate cancer as well as those who have debilitating bone metastases. In this paper, we focus on the historical development and phenotypic descriptions of mouse models used to study prostate cancer. We also comment on how closely each model recapitulates human prostate cancer.